2003
DOI: 10.1097/01.tp.0000044111.12370.ed
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal transplantation on small vessel reactivity1

Abstract: In rat renal transplantation, renal resistance vessel responsiveness to constrictor or dilator stimuli is altered. Extrarenal small vessel function is not affected. The changes in function of renal resistance vessels are not explained by reduction of nephron mass, denervation, ischemia, or chronic rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
0
21
1
Order By: Relevance
“…Besides mesenteric resistance arteries, renal resistance arteries may also be affected and this may in part contribute to CsA-induced nephrotoxicity and renal vasculopathy. However, our results are to some degree inconsistent with findings that postulated that resistance vessels obtained from transplanted kidneys were more sensitive to NE [27]. The findings of a decreased sensitivity to noradrenaline are in contrast to previous reports of an enhanced vascular sensitivity to adrenergic agonists in the presence of CsA: intramuscular administration of surplus doses of CsA (20 mg/kg/day) for 7 days enhanced vasoconstriction in response to noradrenaline [28].…”
Section: Discussioncontrasting
confidence: 57%
“…Besides mesenteric resistance arteries, renal resistance arteries may also be affected and this may in part contribute to CsA-induced nephrotoxicity and renal vasculopathy. However, our results are to some degree inconsistent with findings that postulated that resistance vessels obtained from transplanted kidneys were more sensitive to NE [27]. The findings of a decreased sensitivity to noradrenaline are in contrast to previous reports of an enhanced vascular sensitivity to adrenergic agonists in the presence of CsA: intramuscular administration of surplus doses of CsA (20 mg/kg/day) for 7 days enhanced vasoconstriction in response to noradrenaline [28].…”
Section: Discussioncontrasting
confidence: 57%
“…Similarly, sympathetic denervation in transplanted kidneys results in a significant decrease in local norepinephrine concentrations (28), with a potential effect on intrarenal oxygen bioavailability. However, experimental studies suggest that the medullary blood flow may be insensitive to sympathetic nerve activity (25) and that changes in renal vascular resistance are not explained by denervation (27). As far as CNI use and oxygen bioavailability are concerned, we have been unable to show a correlation between the dose and/or the blood level of CNIs and MR2* or CR2* values in both acute (20) and chronic allograft dysfunction (current study, data not shown).…”
Section: Discussionmentioning
confidence: 66%
“…For systemic inhibition of NHE-3, the newly developed inhibitor #4167, which is highly specific for NHE-3, was used [23,24]. NHE-I solution was prepared by dissolving it in sterile water just before the experiment.…”
Section: Nhe-3 Inhibitor Administration and Minipump Implantationmentioning
confidence: 99%